Pengembangan Model Manajemen Kinerja Strategik pada Koperasi Pegawai Republik Indonesia di Jawa Timur - F. Danardana Murwani; H. Suharto , S.M. (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
The research was intended to produce an empowerment model for improving the performance of public employee cooperative (KPRI). The model is called as the KPRI’s Strategic Performance Management (SPM) model. The research was designed by using developmental research design during two phases. The research is the first one and the output is the draft of KPRI’s SPM model. The sample was taken by using a purposive technique including sample of KPRI and personnel sample of KPRI. Four KPRIs, namely KPRI Universitas Negeri Malang, KPRI Budi Pogalan Trenggalek, KPRI Keluarga SMPN 1 Sidoarjo, and KPRI Jaya Tuban, were selected as sample of KPRI. Five people were also selected from each KPRI as personnel sample. People were involved in field information collecting, namely assessing the implementation level of main elements of the KPRI’s SPM model. The result showed that in general, the implementation level accomplished the high level, but not equal in four KPRIs. Expert judgment was involved in validating the draft.Keywords: manajemen kinerja strategik, expert judgment, KPRI